GIANT FUSIFORM ANEURYSM ARISING FROM FENESTRATED POSTERIOR CEREBRAL ARTERY and BASILAR TIP VARIATION: CASE REPORT - Zanini, Marco Antonio [UNESP]; Pereira, Vitor M.; Jory, Mauricio; Caldas, José Guilherme Mendes Pereira [UNESP] (Lippincott Williams & Wilkins, 2009)
OBJECTIVE: A giant fusiform aneurysm in the posterior cerebral artery (PCA) is rare, as is fenestration of the PCA and basilar apex variation. We describe the angiographic and surgical findings of a giant fusiform aneurysm in the P1-P2 PCA segment associated with PCA bilateral fenestration and superior cerebellar artery double origin.CLINICAL PRESENTATION: A 26-year-old woman presented with a 2-month history of visual blurring. Digital subtraction angiography showed a giant (2.5 cm) fusiform PCA aneurysm in the right P1-P2 segment. The 3-dimensional view showed a caudal fusion pattern from the upper portion of the basilar artery associated with a bilateral long fenestration of the P1 and P2 segments and superior cerebellar artery double origin.INTERVENTION: Surgical trapping of the right P1 -P2 segment, including the posterior communicating artery, was performed by a pretemporal approach. Angiograms performed 3 and 13 months after surgery showed complete aneurysm exclusion, and the PCA was permeated and filled the PCA territory. Clinical follow-up at 14 months showed the patient with no deficits and a return to normal life.CONCLUSION: To our knowledge, this is the first report of a giant fusiform aneurysm of the PCA associated with P1-P2 segment fenestration and other variations of the basilar apex (bilateral superior cerebellar artery duplication and caudal fusion). Comprehension of the embryology and anatomy of the PCA and its related vessels and branches is fundamental to the decision-making process for a PCA aneurysm, especially when parent vessel occlusion is planned.
Keywords: Basilar variation; Dissecting aneurysm; Duplicated artery; Posterior cerebral artery aneurysm